Survivor, Warrior, Mother, Savior: The Evolution of the Female Hero In Apocalyptic Science Fiction Film of the Late Cold War - Faithful, George (Implicit religion, 2016)
The late Cold War saw the advent of a new paradigm of woman as hero in apocalyptic English-language science fiction film at its intersection with the horror and action sub-genres. In contrast to the helpless, villainous, and overly sexualized female characters before them, the Alien films' Ellen Ripley and the Terminator franchise's Sarah Connor represented practical, courageous women who saved humanity through their actions. These ostensibly secular narratives were rich with religious themes such as incarnation, kenosis, resurrection, faith seeking understanding, messianic expectation, virgin birth, free will, fate, evil, prophetic forewarning, and salvation. They were foundational in establishing, in effect, a humanistic mythos.